Membangkitkan Semangat Interaksi Sosial dengan Anak Berkebutuhan Khusus - Zega, Putri Juniman; Ritonga, Fajar Utama; Suriadi, Agus (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2024)
Social interaction is an important aspect in the development of every individual, including children with special needs. For children with special needs, social interaction requires understanding, patience and a sensitive approach. Special education experts and psychologists emphasize the importance of social interaction for children with special needs to develop social skills, empathy, and healthy relationships with others. This Field Work Practice (PKL) activity was carried out by Social Welfare Students of FISIP USU at Terang Sukacita Abadi Orphanage, Medan City. For approximately 3 months, students carry out Project Based Learning (PBL) which aims to raise the spirit of social interaction of children with special needs. Through social work methods, students attempt to change or restore the social functioning of clients, in this case children with special needs. The main focus of this activity is to create a supportive environment where children with special needs can interact with peers and get support from adults who understand their needs. By encouraging social interaction, it is hoped that children with special needs can improve their ability to communicate, build relationships, and develop social skills that are important for their overall development.